Prevalence of hypertension in individuals who sought care at the family health strategy in a city of southeastern Brazil - Osvaldo Costa Moreira; Nathália Faria Guimarães; Cláudia Eliza Patrocínio de Oliveira; Leonice Aparecida Doimo (Universidade Estadual de Maringá, 2014)
This study aimed to verify the prevalence of hypertension among individuals who sought care at the Family Health Strategy (FHS) units, registered in Basic Attention Information System (BAIS), in a city ofSoutheasternBrazil, classified by gender and age. Were evaluated 12,636 individuals who underwent clinical evaluation in ESF units of Viçosa,MinasGeraisState, in the first half of 2011. Data were collected from files registered in BAIS. Statistical analysis consisted of descriptive analysis and calculation of odds ratios according to gender, with a confidence interval of 95% (CI95%). The prevalence of hypertension was 13.40%, in men the prevalence was 11.21%, and in women, 15.53%. The odds ratio indicated that women are 1.46 times more likely CI95% (1.27, 1.52) to present hypertension than men. In both sexes, the prevalence of hypertension increases with advancing age, especially in the age groups above 50 years. We conclude that the prevalence of hypertension was below the national average, being higher in women and increases along with advancing age.